Revisiting the Link Between HLA‐DRB1 Alleles and Autoantibodies in Rheumatoid Arthritis: Association of non‐Shared Epitope Alleles *09 and *15 With High Levels of Anti–Citrullinated Peptide/Protein Antibodies - Denis Lagutkin; Luis Panaifo; Ahmad‐Fauzi Nurul‐Aain; Lena Israelsson; Monika Hansson; Karin Lundberg; Lars Alfredsson; Johan Askling; RACI consortium; Lars Klareskog; Chun‐Lai Too; Leonid Padyukov (ACR Open Rheumatology)
Objective Autoantibodies serve as essential clinical biomarkers and may indicate etiological mechanisms in rheumatic diseases. In light of the increasing knowledge concerning the diversity and biologic implications of anti–citrullinated peptide/protein antibodies (ACPAs), we have re‐evaluated the association between the ACPA response and the HLA‐DRB1 allelic groups, known to represent a major genetic risk factor for rheumatoid arthritis (RA). Methods We explored a collection of 4,392 well‐characterized incident patients with RA of White European descent from the Epidemiological Investigation of Rheumatoid Arthritis (EIRA) new‐onset RA study, as well as 1,199 cases of patients with RA of Southeast Asian origin from the Malaysian EIRA study. We focused on a quantitative analysis of the levels of anti–cyclic citrullinated peptide IgG antibodies, including those falling below the diagnostic threshold. Results Our data show that non‐shared epitope alleles HLA‐DRB1*09 and *15 exhibit significant associations with ACPA levels. Notably, these novel associations were independent of ethnicity. To validate our findings, we conducted an additional replication study in an independent pool of 4,109 patients with RA of White European origin. Conclusion These results indicate a new, previously overlooked, role for the HLA locus in the regulation of the levels of ACPA RA‐specific autoantibodies that goes beyond the shared epitope‐defined gene variants.